Preparation and Characterization of Chitosan-Gelatin-Glycerol Biocomposite for Primary Wound Dressing - Suryati, Suryati; Meriatna, Meriatna; Sulhatun, Sulhatun; Lestari, Dwi Ayu (Malikussaleh University, Aceh, Indonesia, 2022)
This study aimed to examine the laboratory-based preparation of chitosan-gelatin bio-composite with the addition of glycerol as an additive to improve its quality which could be further applied for primary wound dressing. The method consisted of three stages; the first was the preparation of raw materials, the second was the preparation of the bio-composites, and the last was the characterization. In this study,chitosan 90.2% DD and gelatine (dissolved in 1% acetic acid) were blended at volume ratios v/v (30:70), and glycerol was added into blended at five different volume 20, 25, 30, 35, 40, 45 (mL) respectively. The biocomposites is then shaped in a glass mold, allowed to at room temperature for 24 hours, and dried in oven at 50oC for 48 hours. The chitosan-gelatin-glycerol bio-composites was smooth, flexible, transparent thin sheet and non-porous. The optimum thickness (4.01 mm) was obtained from a bio-composite with chitosan-gelatin-glycerol ratio of 30:70:45. The same composition rasio was found to have the liquid absorbance reaching 140.34%. The bio-composite with a chitosan-gelatin-glycerol ratio of 30:70:45 also had the highest swelling ability in saline (168.06%). The functional group analysis using Fourier Transform Infrared (FT-IR) spectroscopy revealed the possession of hydroxyl (O-H) and carbonyl (C-O) functional groups suggesting its good biodegradability and environmentally friendly properties. Taken altogether, the results imply the wound dressing bio-composite is hydrophilic. Based on the results of characteristic testing, it is shown that the chitosan-gelatin-glycerol biocomposite has the potential to be applied as a primary wound dressing, which is ideal for wound healing and protection.